Examining Study Habits as a Potential Mediator Between Time Management and Academic Achievement Among BS Office Administration Students at a State University in Cavite - Baco, Arriane Jade; Balboa, Jasmine Joy; Callanta, Jovell; Montemayor, Angelene; Parce, Steve Andrei; Quirap, Marvian Gayle; Ramos, Julie Ann; Ardina, Aileen; Nuestro, Jo Anne; Bacones, Nepthali (International Journal of Education, Research, and Innovation Perspectives, 2026)
Academic achievement remains a critical indicator of student success in higher education, with time management and study habits frequently identified as important determinants of academic achievement. However, limited research has examined the mediating role of study habits in the relationship between time management and academic achievement among Bachelor of Science in Office Administration (BSOA) students. This study investigated the levels of time management, study habits, and academic achievement and examined the direct and indirect relationships among these variables. A quantitative descriptive-correlational research design was employed involving 224 BSOA students from a state university in Cavite. Data were gathered using modified questionnaires and analysed by Partial Least Squares Structural Equation Modelling (PLS-SEM). The measuring model was tested for reliability and validity using Cronbach’s alpha, composite reliability, average variance extracted, and discriminant validity. The results indicated that the students’ time management was at a good level, study habits at a moderate level, and academic achievement at an excellent level. The findings of the structural model showed that the study habits had a substantial impact on the academic and time management had a big impact on the academic achievement. But time management did not have any meaningful effect on the habits of study. In addition, study habits did not have a significant mediating effect between time management and academic achievement. The study shows that time management and study habits are independent predictors of academic achievement and that study habits do not mediate between time management and academic achievement. These results provide empirical data for the development of programs that attempt to increase students’ academic achievement by improving their time management and study skills.